Impact Evaluation of Sustainable Land Management (SLM) in Tunisia: The Efficiency of GIS and Remote Sensing Data. - Fradi, Fajr (2017)
The challenge of land degradation is particularly felt in Tunisia, where soil erosion rate is high and affects 50% of its total surface. The land and water conservation has been the focus of national policies for almost 30 years, With a climatic variety going from arid -approximately 77% of the whole area -to semi-arid, the degradation of land and water resources remains a challenge. Multiple national strategies have been implemented since 1990, with the support of law enforcement to decrease this threat, and a special unit (DG-ACTA), which was created in 2001 to support the Ministry of Agriculture. The overall measures taken led to an increase of SLM practices in the Tunisian landscape for better performance.